1970
DOI: 10.1071/zo9700315
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature on the post-diapausal development and survival in the aestivating eggs of Halotydeus destructor (Acari : Eupodidae)

Abstract: After diapause development is complete, moistened aestivating eggs of H. destructor develop successfully within the temperature range 5-20.5C. The rate of development up to the deutovum stage increases with temperature up to about 20C and then rapidly decreases. Eggs will tolerate temperatures between 25 and 31.5C for up to 53 days without undergoing morphogenesis, but this treatment retards subsequent development at 16C. Exposure to alternating temperatures accelerates the rate of development but, if the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 0 publications
2
47
0
Order By: Relevance
“…Halotydeus destructor are not found in January or February as the oversummering eggs will generally not have had sufficiently hot conditions to terminate diapause (Wallace 1970a). Temperature has a profound influence on the development of aestivating eggs of H. destructor (Davidson and Swan 1943;Norris 1950;Wallace 1970b). Wallace (1970b) found that the pre-deutovum stage of aestivating eggs was more sensitive to higher temperatures than the shorter deutovum stage.…”
Section: Background Informationmentioning
confidence: 98%
See 4 more Smart Citations
“…Halotydeus destructor are not found in January or February as the oversummering eggs will generally not have had sufficiently hot conditions to terminate diapause (Wallace 1970a). Temperature has a profound influence on the development of aestivating eggs of H. destructor (Davidson and Swan 1943;Norris 1950;Wallace 1970b). Wallace (1970b) found that the pre-deutovum stage of aestivating eggs was more sensitive to higher temperatures than the shorter deutovum stage.…”
Section: Background Informationmentioning
confidence: 98%
“…Temperature has a profound influence on the development of aestivating eggs of H. destructor (Davidson and Swan 1943;Norris 1950;Wallace 1970b). Wallace (1970b) found that the pre-deutovum stage of aestivating eggs was more sensitive to higher temperatures than the shorter deutovum stage. The favourable temperature range for morphogenesis in the pre-deutovum stage is 5°C to about 20°C, with optimum developmental rates occurring around 19°C.…”
Section: Background Informationmentioning
confidence: 98%
See 3 more Smart Citations